2015
DOI: 10.1186/s12862-015-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid divergence and diversification of mammalian duplicate gene functions

Abstract: BackgroundGene duplication provides raw material for the evolution of functional innovation. We recently developed a phylogenetic method that classifies evolutionary processes driving the retention of duplicate genes by quantifying divergence between their spatial gene expression profiles and that of their single-copy orthologous gene in a closely related sister species.ResultsHere, we apply our classification method to pairs of duplicate genes in eight mammalian genomes, using data from 11 tissues to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
104
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(131 citation statements)
references
References 43 publications
25
104
2
Order By: Relevance
“…Alternatively, the rare cases of subfunctionalization of plant duplicate genes may be due to the stringent criteria of our methodology for identification, which cause some subfunctionalization cases to be classified into conservation and specialization categories. One possible solution might be to conduct the same analysis using expression data from more tissues (Assis and Bachtrog, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the rare cases of subfunctionalization of plant duplicate genes may be due to the stringent criteria of our methodology for identification, which cause some subfunctionalization cases to be classified into conservation and specialization categories. One possible solution might be to conduct the same analysis using expression data from more tissues (Assis and Bachtrog, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the evolutionary processes maintaining duplicate genes in A. mellifera (Assis and Bachtrog , ). We found that there were 63 cases of conservation, 28 cases of neofunctionalization (15 of D1 copy, the duplicate with higher sequence similarity to the single copy ortholog, 13 of D2 copy, the duplicate with lower sequence similarity to the single copy ortholog), nine cases of specialization, and no cases of subfunctionalization.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we identified no cases of subfunctionalization. It is notable that prior studies of this type also found that conservation was one of the most common mechanisms maintaining gene duplicates in mammals and plants (Assis and Bachtrog ; Wang et al. ).…”
Section: Discussionmentioning
confidence: 96%
“…; Farré and Albà ; Assis and Bachtrog ; Assis ; Assis and Bachtrog ; Jiang and Assis ) divergence that often generates novel (Chen et al. ; Assis and Bachtrog ; Assis ; Assis and Bachtrog ; Jiang and Assis , ) and essential (Holland et al. ; Taylor and Raes ; Liao and Zhang ; Chen et al.…”
mentioning
confidence: 99%
“…; Chen et al. ; Farré and Albà ; Assis and Bachtrog ; Assis ; Assis and Bachtrog ; Jiang and Assis ) often diverge soon after duplication, suggesting that any initial redundancy between duplicates is rapidly abolished. Moreover, if duplicate gene functions are in fact redundant, then deleterious effects of the deletion of one copy should be compensated by the presence of another copy.…”
mentioning
confidence: 99%